The Barriers to Myocardial Infarction Patients\' Participation in Cardiac Rehabilitation Program - Ardeshir Afrasiabi-Far; Parkhideh Hosseini; Masoud Fallahi-Khoshknab; Fariideh Yaghmaei (University of Social Welfare and Rehabilitation Sciences, 2008)
Objective: Cardiac rehabilitation increases quality of life, decreases recurrence, and improves physical performance and psychological status. This report aimed to examine barriers to patients' participation in cardiac rehabilitation program. Materials & Methods: This paper is a party of a larger grounded theory study. Eighteen patients with first time myocardial infarction, three cardiologists, and three cardiac nurses were selected as purposeful and theoretical sampling. Semi-structure interviews were used for data collection. Using Strauss and Corbin's (1998) grounded theory approach, the data were analyzed. The trustworthiness of data is confirmed using Lincoln and Guba's criteria. Results: The majority of patients had not participated in cardiac rehabilitation programs. Barriers to patients' attendance in cardiac rehabilitation categorized in four main categories known as individual, sociocultural, economic, and health care system-related factors.  Conclusion: The majority of the barriers to patients' participation in cardiac rehabilitation are modifiable that their alteration can facilitate patients' attendance in cardiac rehabilitation programs.